Chemical Isolation, Characterization And Biological Properties Of Some Native Remedies - Tze-Fung, Yvonne Tan (1979)
A preliminary microbiological screening was performed on five local Malaysian herbs which were claimed to possess certain medicinal values. These herbs were the pods of Abelmoxhue eeoulentue, the flowers of Hibieeue rosaeineneie, the plants of Mimosa pudica, the leaves of Parkia javaniaa and the leaves of Pel.tophoxum ptierocarpum, Abelmoxhus eecul.entue was the only herb that exhibited no antibacterial activity at the doses tested while the rest of the four herbs showed promising results in their antibacterial activity by both ditch-plate and hole-plate methods. Results from the bioassay of herbal extracts and antibiotics (Potassium Penicillin V and Streptomycin Sulphate) showed linear relationships in the dose response curves, however, due to lack of parallelism between the standards and extracts used, it indicated that the herbal extracts might possess a different antibacterial mode of action as that of the standard antibiotics.